Loss of Vision after Laser Peripheral Iridotomy: A Case Report: Doi: 10.36351/pjo.v37i4.1268 - Mahar, P S; Rehman, Asma; Memon, Abdul Sami (Pakistan Journal of Ophthalmology, 2021)
Laser Peripheral Iridotomy (LPI) is a common laser procedure carried out in patients with narrow or occluded irido-corneal angles at risk of developing angle closure glaucoma. Nd-YAG and Argon laser are used sequentially in our local population to create an iridotomy. Posterior segment complications are rare after this procedure and generally can occur due to direct laser induced damage. We report a 44-year old patient, who had LPI performed on his both eyes. Post laser patient complained of reduced vision in his left eye and was evaluated in our glaucoma clinic. On examination, his vision was 20/25 unaided in his right eye and 20/60 in his left eye with no further improvement. Optical coherence tomography (OCT) revealed presence of cystoid macular edema (CME) in his left eye responsible for his reduced vision. Key Words: Laser Peripheral Iridotomy, Cystoid Macular Edema, Argon Laser.